Composite Noble‐Metal Films/H+‐Conducting Solid‐Polymer Electrolyte Assemblies: The Nitrate‐Reduction Activity in an Asymmetric Sandwich‐Type Reactor. Issue 11 (31st July 2015) - Hasnat, Mohammad A.; Islam, Muhammad Amirul; Aoun, S. Ben; Safwan, Jamil A.; Rahman, Mohammed M.; Asiri, Abdullah M.
Abstract: Asymmetric (Pt|Nafion|Pt–Pd–Cu) assemblies were fabricated to study the nitrate‐reduction reaction (NRR) at the cathode surface. The influence of the material composition, supplied current, and applied potential on the reactivity, kinetics, and product selectivity were thoroughly investigated. The cathode assembly consisting of 54 atom % Pt showed enhanced reactivity both in binary (Pt–Pd; k 1 ≈10.7×10 −3  min −1 ) and ternary (Cu–Pt–Pd; k 1 ≈28.6×10 −3  min −1 ) states. This composition was found to be highly nitrite‐selective (80 % in the binary state and 53 % in the ternary state). The mechanistic studies revealed that the reduction of nitrate ions to ammonia proceeded through a catalytic hydrogenation reaction followed by electrochemical hydrogen generation. Abstract : It′s what′s inside that counts : The catalyst composition has been found to determine the reactivity and product selectivity of electrocatalytic nitrate‐reduction reactions. The catalytic performance of both bimetallic (Pt–Pd) and trimetallic (Cu–Pt–Pd) assemblies was investigated. Reduction of NO3 − to NH3 proceeded through a hydrogenation reaction followed by electrochemical hydrogen generation on the Pt–Pd surface. Hydrogen reduced NO3 − to NH3 catalyzed by Cu (see scheme).